2014
DOI: 10.1371/journal.pone.0099790
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Tissue Zinc in Epithelial Malignancies: A Meta-Analysis

Abstract: Background and ObjectivesCurrent studies give us inconsistent results regarding the association of neoplasms and zinc(II) serum and tissues concentrations. The results of to-date studies using meta-analysis are summarized in this paper.MethodsWeb of Science (Science citation index expanded), PubMed (Medline), Embase and CENTRAL were searched. Articles were reviewed by two evaluators; quality was assessed by Newcastle-Ottawa scale; meta-analysis was performed including meta-regression and publication bias analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 103 publications
(129 reference statements)
2
79
0
Order By: Relevance
“…The potential reasons for a variable difference in tissue Zn level between PCa and BPH in studies may be-unwanted possible representative tissue sampling errors or ethnic related. Despite the evidence [29] for decrease in serum and tissue Zn as well as significance of zinc in PCa in experimental studies, the epidemiological data have shown mixed results between zinc status and PCa, varying from direct [30][31][32] to inverse [33][34][35] correlation and no significant correlation [7,36]. Higher levels of zinc supplementation have been shown to increase prostatic tissue zinc levels and induce intraepithelial carcinoma prostate in murine model [37].…”
Section: Discussionmentioning
confidence: 99%
“…The potential reasons for a variable difference in tissue Zn level between PCa and BPH in studies may be-unwanted possible representative tissue sampling errors or ethnic related. Despite the evidence [29] for decrease in serum and tissue Zn as well as significance of zinc in PCa in experimental studies, the epidemiological data have shown mixed results between zinc status and PCa, varying from direct [30][31][32] to inverse [33][34][35] correlation and no significant correlation [7,36]. Higher levels of zinc supplementation have been shown to increase prostatic tissue zinc levels and induce intraepithelial carcinoma prostate in murine model [37].…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in zinc is observed early in the course of prostate cancer development, and the trend continues toward castration-resistant disease (40). Several studies showed the depression of zinc concentration in the cancerous human lung tissues, especially in the small cell lung cancer, the most malignant form in lung cancer (17,19,41). For ovarian cancer, serum zinc decreased in patients subsequently diagnosed with ovarian cancer, whereas in tumor tissue, the concentration of zinc also decreased (20,21).…”
Section: H72cd2-hd2mentioning
confidence: 99%
“…[15] Many studies showed a correlation between low serum Zn levels and the risk for developing BC, others, revealed the erythrocytes Zn levels was significantly low in women with BC compared with normal women as it more correctly that didn't attributed to dietary Zn deficiency. [9] In the current study, almost patients had a Zinc supplement with their diet which declared in the questioner formula, however, serum zinc was significantly low that reflect a defective zinc metabolism in such patients, there was a high level of regulation of zinc importer (Zip) and transporter (ZnT) proteins families which enable the cellular zinc homeostasis (Chasapis CT, et al, 2014 Dec) [16] and several of these proteins appear to be disturbed in BC cells.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…[9] In the current study, almost patients had a Zinc supplement with their diet which declared in the questioner formula, however, serum zinc was significantly low that reflect a defective zinc metabolism in such patients, there was a high level of regulation of zinc importer (Zip) and transporter (ZnT) proteins families which enable the cellular zinc homeostasis (Chasapis CT, et al, 2014 Dec) [16] and several of these proteins appear to be disturbed in BC cells. In Another complex issue was appeared when dealing with the regulation of serum Zn levels compared to its levels in the corresponding tumor tissues of cancer patients, breast biopsies from cancer patients have significantly higher Zn levels compared with normal breast tissues [9] , on the other hand, the majority of tumors, zinc level decrease in both serum and tissue to certain extent and it is uncertain, whether low serum level is a result of tumor, chronic stress or of both of these effects, that, leads to relocation of zinc between body compartments, in addition, chronic inflammation is a common mark of cancer which might be an important mechanism of serum zinc level decrease [15] , on the other hand, examination of BC biopsies as well as cultured cells revealed abnormal expression of multiple proteins that play a role in zinc homeostasis. [9] Moreover, abnormal functioning of both ZnTs and ZIPs as well as the imbalances in their activities could play a role in Zn dyshomeostasis and cancer development.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%